Tunable Cinchona‐Based Thioureas‐Catalysed Asymmetric Epoxidation to Synthetically Important Glycidic Ester Derivatives. Issue 6 (7th March 2017) - Meninno, Sara; Zullo, Luca; Overgaard, Jacob; Lattanzi, Alessandra
Abstract: A novel class of synthetically important glycidic esters has been obtained via an asymmetric epoxidation of trans ‐α‐cyano‐α, β‐unsaturated esters catalysed by a multifunctional Cinchona alkaloid‐derived thiourea/ tert ‐butyl hydroperoxide (TBHP) system. The glycidic esters, isolated in excellent yield with complete trans ‐diastereocontrol and high enantioselectivity, proved to be versatile building blocks to access challenging small targets bearing a quaternary stereocenter. Abstract :